ACE2 PET to reveal the dynamic patterns of ACE2 recovery in an infection model with pseudocorona virus. Issue 2 (18th January 2023) - Li, Xiao; Yin, Wei; Li, Ao; Li, Danni; Gao, Xiaolong; Wang, Ruizhi; Cui, Bin; Qiu, Shuang; Li, Rou; Jia, Lina; Zuo, Changjing; Zhang, Lan; et al.
Abstract: Due to the COVID‐19 pandemic, a series of sequelae, such as fatigue, tachypnea, and ageusia, appeared in long COVID patients, but the pathological basis was still uncertain. The targeted radiopharmaceuticals were of potential to systemically and dynamically trace the pathological changes. For the key ACE2 protein in the virus‐host interaction, 68 Ga‐cyc‐DX600 was developed on the basis of DX600 as a PET tracer of ACE2 fluctuation and maintained the ability in differentiating ACE and ACE2. In the temporary infection model inhaled with the radio‐traceable pseudovirus in the upper respiratory tract of male humanized ACE2 (hACE2) mice, organ‐specific ACE2 dysfunction in acute period and the following ACE2 recovery in a relatively long period was visualized and quantified by ACE2 PET, revealing a complex pattern of virus concentration‐dependent degree and time period‐dependent tendency of ACE2 recovery, mainly a sudden decrease of apparent ACE2 in the heart, liver, kidneys, lungs, and so on, but the liver was of a quick functional compensation on ACE2 expression after a temporary decrease. ACE2 expression of most organs has recovered to a normal level at 15 days post inhalation, with brain and genitals still of a decreased SUVACE2 ;  meanwhile, kidneys were of an increased SUVACE2 . These findings on ACE2 PET were further verified by western blot. When compared with high‐resolution computed tomography on structural changes and FDG PET on glycometabolism, ACE2 PET was superior in an earlier diagnostic window during infection and more comprehensive understanding of functional dysfunction post‐infection. In the respective ACE2 PET/CT and ACE2 PET/MR scans of a volunteer, the repeatability of SUVACE2 and the ACE2 specificity were further confirmed. In conclusion, 68 Ga‐cyc‐DX600 was developed as an ACE2‐specific tracer, and the corresponding ACE2 PET revealed the dynamic patterns of functional ACE2 recovery and provided a reference and approach to explore the ACE2‐related pathological basis of sequelae in long COVID.